2005
DOI: 10.1111/j.1475-5890.2005.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Affordability of Household Water and Sewerage Services in Great Britain*

Abstract: This paper analyses the problem of water affordability in Great Britain. The use and meaning of the term ‘affordability’ are discussed in relation to the domestic or household customers of the British water industry. Using microeconomic data from the Family Resources Survey, affordability is calibrated by income group and household composition for Scotland, England and Wales. Whilst measurement or calibration is the primary focus of the paper, the related question of the way in which an affordability threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 3 publications
0
25
0
2
Order By: Relevance
“…This benchmark is similar to the OECD recommendation that household water bills not consume more than 3–5% of household income [27,28]. The Unitary Universalist Service Committee advocates for 2.5% of monthly household income [10,26,29] which is similar to the U.S. Environmental Protection Agency (EPA) standard that households spend no more than 2% on water and 4.5% of median household income on both water and wastewater services [30]. The U.S. EPA threshold of 4.5% is similar to the World Bank income benchmark of 5% [1].…”
Section: Assessing and Measuring Water Affordabilitymentioning
confidence: 54%
“…This benchmark is similar to the OECD recommendation that household water bills not consume more than 3–5% of household income [27,28]. The Unitary Universalist Service Committee advocates for 2.5% of monthly household income [10,26,29] which is similar to the U.S. Environmental Protection Agency (EPA) standard that households spend no more than 2% on water and 4.5% of median household income on both water and wastewater services [30]. The U.S. EPA threshold of 4.5% is similar to the World Bank income benchmark of 5% [1].…”
Section: Assessing and Measuring Water Affordabilitymentioning
confidence: 54%
“…The details of which can be found in [13]. Sawkins and Dickie [13] reported that there is no commonly agreed affordability benchmark in the UK. For England and Wales an indicative water affordability measure has been adopted by DEFRA (i.e.…”
Section: General Discussion -Towards An Affordability Benchmarkmentioning
confidence: 99%
“…A 10% fuel poverty threshold has been embedded within various government energy policy statements for several years [3]. The details of which can be found in [13]. Sawkins and Dickie [13] reported that there is no commonly agreed affordability benchmark in the UK.…”
Section: General Discussion -Towards An Affordability Benchmarkmentioning
confidence: 99%
“…The World Bank uses a benchmark set by the Pan‐American Health Organization, that households should spend no more than 5 per cent of their monthly income on water (World Bank, 2001). In the UK, the government considers water tariffs to be unaffordable if expenditure exceeds 3 per cent of household income, which is twice the current median spending ratio on water in the country (Sawkins and Dickie, 2005). A recent Human Development Report (UNDP, 2006) also suggests that no household should spend more than 3 per cent of its income on water.…”
Section: Impacts Of Commercialization Of Urban Water Services In Zambiamentioning
confidence: 99%